Associations of prenatal exposure to phthalates and one phthalate substitute with anthropometric measures in early life: Results from the German LIFE Child cohort study. Issue 5 (September 2021) - Nidens, Nathalie; Krönke, Anna; Jurkutat, Anne; Schlingmann, Maike; Poulain, Tanja; Nüchter, Matthias; Kiviranta, Hannu; Körner, Antje; Vogel, Mandy; Lindh, Christian; Bornehag, Carl-Gustaf; Kiess, Wieland
Abstract : Exposure to phthalates is widespread and especially early life stages represent a critical window of exposure. In the present study, we investigated the effect of prenatal exposure to phthalates on birth outcomes and weight development in early life. In 130 mother–child pairs, we estimated the association of concentrations of 13 phthalates in spot-urine samples collected during pregnancy and birth outcomes and weight gain in the first two years of life using robust linear regression. High molecular weight phthalates were inversely associated with birth weight in girls but not in boys. Thus, prenatal exposure to phthalates may affect birth weight in a sex-specific manner.